Tooth coronal index (TCI), antegonial angle, and antegonial depth measurement for age estimation using digital panoramic radiograph - Priyanka Tidke; Sunita Kulkarni; Vaishali Agrawal; Ullas Saxena; Rucha Pandharipande (Wolters Kluwer Medknow Publications, 2019)
Introduction and Aim: Age estimation in living individuals is a relatively recent area of applied research within the forensic sciences. Tooth coronal index (TCI) method of age estimation is based on the relationship of age and size of pulp on dental radiographs. This study was an attempt to device simple, cost-effective method to perform morphometric analysis of dental pulp for age estimation. Materials and Methods: In all, 200 subjects were studied for this study. They were classified into four groups (21-30, 31-40, 41-50, and 51-60 years). Subjects then had undergone digital radiographic procedure [radiovisiography (RVG) and orthopantomogram (OPG)], and morphometric analysis (TCI, antegonial angle, and depth) was done. Results: On analysis of complete models with TCI, antegonial angle, and depth, there were 21 (42%) cases with predicted age within ± 5 years in the test data set. In the complete data set (n = 200), 78 (39%) cases were predicted with age within ± 5 years. The models derived for the second premolar and with TCI, antegonial angle, and antegonial depth were better predictor of age when compared with model with only single parameter. On predictions based only on TCI, both the OPG and RVG methods were at par with regard to the overall prediction. Conclusion: There are no significant differences in correlation of age with TCI using OPG and RVG. Correlation of age when three parameters (TCI, antegonial angle, and antegonial depth) are combined is more significant when compared with TCI alone.